The effects of sunlight on bacteria - Blachly, Charles Dallas (My University, 1902)
Introduction: Bacteria are one celled microscopic plants which reproduce by fission and are propagated by sporulation. In the evolutionary classification of plants they hold the following positions. Plant Kindgom, Sub Kingdom – Thallophyta, Division II – Euthallophyta or true thallophytes, Sub Division 1 – Schyomycetes, fission fungi or bacteria. As the above classification indicates the bacteria are supposed to be degenerate forms of fission plants, probably springing from the algae. Most of them being parasitic or saprophytic they have lost their power of photosynthesis, it in this degenerate form being no longer of use to them. Others of the nitrifying group derive their energy in an unknown way from certain mineral salts. As these plants gradually formed the saprophytic habit they lost the need of light to assist in forming starch. Those that burrowed into the interior of the medium in which they were growing were more protected from the external world than those living upon the surface. The result is their descendants which of course also inherited the tendency to leave the surface were more successful in the struggle for existence than those living upon the surface or exterior.
Citation: Blachly, Charles Dallas. The effects of sunlight on bacteria. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Bacteria; Photosynthesis; Theses